Kenosis and the nature of the Persons in the Trinity - D.T. Williams (Koers : Bulletin for Christian Scholarship, 2004)
Philippians 2:7 describes the kenosis of Christ, that is Christ’s free choice to limit himself for the sake of human salvation. Although the idea of Christ’s kenosis as an explanation of the incarnation has generated considerable controversy and has largely been rejected in its original form, it is clear that in this process Christ did humble himself. This view is consistent with some contemporary perspectives on God’s self-limitation; in particular as this view provides a justification for human freedom of choice. As kenosis implies a freely chosen action of God, and not an inherent and temporary limitation, kenosis is consistent with an affirmation of God’s sovereignty. This view is particularly true if Christ’s kenosis is seen as a limitation of action and not of his attributes. Such an idea does not present problems concerning the doctrine of the Trinity, specifically regarding the relation between the economic and the immanent nature of the Trinity. The Trinitarian doctrine, on the contrary, indeed complements this idea – specifically the concept of perichoresis (the interrelatedness among the Persons of the Triniy and the relation between the two natures of Christ).